Building The Strengthening of Environmental Protection and Management In The Industrial Revolution-Era 4.0 - Gunawan, Adi; Nadir, Nadir; Fatkhurohman, Fatkhurohman (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Environmental protection is no longer negotiable, in Indonesia and internationally the destruction of the environment due to mining and deforestation has reached an alarming threshold and threatens the lives of future generations. The actions that have been taken and the existence of institutions / organizations in the field of environment are not able to make a maximum contribution to environmental protection.Purposes of the Research: The purpose of this research is to find a concept of strengthening environmental protection that is more effective and efficient and can be applied in preventing massive environmental damage both on a national and international scale and efforts to rehabilitate environmental damage that can be carried out by local communities with government support in the future, especially in the era of the industrial revolution 4.0.Methods of the Research: This research is a qualitative research that examines legal policies (normative legal research) related to the environment. The data used is secondary data in the form of literature from the opinions of experts as well as the results of previous studies relevant to the topic of the problem. The collected data is grouped according to the stages and systematics of research and the flow of discussion then analyzed by providing explanations that are strengthened by theories from legal experts, especially in the environmental field.Results of the Research: Strengthening environmental protection and management in the industrial era 4.0 can be done in two ways, namely: (1) strengthening the role of the community initiated and fully supported by the government by making the community a partner in environmental management (2) Institutional strengthening in environmental protection and management, namely by making customary / community institutions as one of the main elements in policies related to the environment.